2013
DOI: 10.7314/apjcp.2013.14.2.1061
|View full text |Cite
|
Sign up to set email alerts
|

Spect-guidance to Reduce Radioactive Dose to Functioning Lung for Stage III Non-small Cell Lung Cancer

Abstract: Objective: To investigate the treatment effect of additional information obtained by single photon emission computed tomography (SPECT) lung perfusion imaging (LPI) in the radiotherapy planning process for patients with stage III non-small cell lung cancer (NSCLC). Methods: 39 patients with stage III NSCLC were enrolled. Gross tumor volume (GTV) was outlined by SPECT/CT images, SPECT-LPIs being used to define functional lung (FL) and non-functional lung (NFL) regions. Two sets of IMRT plans were designed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Shioyama et al showed that the median reductions of MLD were 2.2 Gy (17.6-14.5) and 4.2 Gy (16.0-11.8) by functional plans incorporating 50% and 90% thresholds with perfusion SPECT/CT, respectively, compared with those in the anatomic plans 19 . The other studies showed similar results 21,23,24 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Shioyama et al showed that the median reductions of MLD were 2.2 Gy (17.6-14.5) and 4.2 Gy (16.0-11.8) by functional plans incorporating 50% and 90% thresholds with perfusion SPECT/CT, respectively, compared with those in the anatomic plans 19 . The other studies showed similar results 21,23,24 .…”
Section: Discussionsupporting
confidence: 72%
“…Among the 13 studies using SPECT, only three mentioned the scanning protocols including projections, acquisition times, and matrix sizes 3 , 15 , 16 . Five studies described inadequate scanning information 17 20 , and the remaining five, including two conference papers, did not mention any information 4 , 21 23 . The two studies using PET provided detailed information 24 , 25 .…”
Section: Resultsmentioning
confidence: 99%